Att dansa historia : Elevers och lärares upplevelser av dans som metod för annat lärande - Gustafson-Asp, Caroline; Sandor, Ida (2015)
The aim of this studyhas been the development of the method To dance history and its validity. How the subject of history can be taught through dance. We want to create knowledge of how such integration may appear.The survey was conducted in two parts. The first part with the method To dance history, that is danced history lessons. The second part was an interview study in which knowledge by the method was discussed with students and teachers. The method is tested in elementary school, third grade, one in central Sweden and one in Northern Sweden, as well with their teachers. Both classes were new to the dance as a method for other learning.The teachers felt that there has been a rewarding and fun method that benefited the students knowledge by being given the opportunity for a different way of learning. The teachers believe that knowledge is deepened if more learning styles are used in teaching. They are in favor of learning in with the whole body and therefore experience to dance history is a relevant method. The objectives of history becomes clearer for the students when using the method To dance history. Because they get to see, hear and make history. As the phenomemology mean we learn with the lived body. The intellect and the physical body can not be separated (Ferm 2008 Alerby 2009). Validerat; 20150615 (global_studentproject_submitter)